2020
DOI: 10.1007/s13205-020-02447-3
|View full text |Cite
|
Sign up to set email alerts
|

Spectral quality and temporary immersion bioreactor for in vitro multiplication of Eucalytpus grandis × Eucalyptus urophylla

Abstract: Spectral quality is an important factor for in vitro development of explants in a bioreactor system. Based on the need to optimize micropropagation for E. grandis × E. urophylla clones, the aim of the study was to assess the spectral quality of in vitro multiplication in temporary immersion bioreactor (TIB). The tissue used to generate the explants (i.e., the nodal segment with 1 cm of length and two axillary bud without leaves) was previously in vitro established and multiplied, it derived from ministumps of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Many studies have shown the superiority of white light sources for in vitro plant development (Batista et al 2018;Abiri et al 2020), although responses vary. Genotypic differences in the in vitro development have also been reported in different clones of Eucalyptus, such as Eucalyptus grandis × E. urophylla (Souza et al 2020a;Miranda et al 2020), Eucalyptus benthamii (Brondani et al 2018), and Eucalyptus globulus (Oliveira et al 2016). Thus, different results are observed for explants in the in vitro multiplication stage, the response varying according to the genotype and the culture conditions (e.g., spectral quality).…”
Section: Effect Of Spectral Quality On In Vitro Multiplicationmentioning
confidence: 98%
See 3 more Smart Citations
“…Many studies have shown the superiority of white light sources for in vitro plant development (Batista et al 2018;Abiri et al 2020), although responses vary. Genotypic differences in the in vitro development have also been reported in different clones of Eucalyptus, such as Eucalyptus grandis × E. urophylla (Souza et al 2020a;Miranda et al 2020), Eucalyptus benthamii (Brondani et al 2018), and Eucalyptus globulus (Oliveira et al 2016). Thus, different results are observed for explants in the in vitro multiplication stage, the response varying according to the genotype and the culture conditions (e.g., spectral quality).…”
Section: Effect Of Spectral Quality On In Vitro Multiplicationmentioning
confidence: 98%
“…Spectral qualities red, blue, yellow, purple and green were provided, under all growth stages, by filtering the light output of the fluorescent light bulbs through double sheets of cellophane (Souza et al 2020a) replaced every cycle. The light spectra were measured using a SPECTRA PEN Z850 portable spectrophotometer (Qubit Systems, Kingston, Ontario, USA).…”
Section: Spectral Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…An immersion frequency of 30 s every 30 min or every 3 h produced the highest number of shoots per explant in Jeffersonia dubia [78] and in Eucalyptus grandis × E. urophylla ( [70] (Table 1). The effect of immersion interval (15 min immersion every 4 h) was more critical in Aquilaria malaccensis shoot cultivation when an increase in the number of shoot regeneration (5.12) and biomass (3.12 g) were obtained compared to 5 min/4 h [48].…”
Section: Immersion Frequency and Biomass Productionmentioning
confidence: 99%